100 → 111 morphological change in KCl crystals grown from Pb2+-doped aqueous solutions. Issue 41 (23rd September 2015) - Pastero, L.; Cossio, R.; Aquilano, D.
Abstract : Sylvite crystals are grown from solution in the presence of lead. An epitaxial model explains both habit and surface modifications. Abstract : KCl f.c.c. crystals generally exhibit a 100 habit when growing from pure aqueous solutions, a richer 100 + 111 morphology being obtained only under well-defined growth temperature and supersaturation. When increasing amounts (less than 2000 ppm) of Pb are put in a supersaturated solution, the KCl growth morphology undergoes a progressive change: 100 → 100 + 111 → 111. Detailed growth patterns have been investigated by means of SEM and AFM, while EDS and XRF analyses allowed us to ascertain that Pb is not only adsorbed on the growing KCl surfaces but also selectively absorbed within the 111 growth sectors. Starting from recent and analogous findings, we tried to interpret the morphological change by means of a geometric and structural model of epitaxy between the 100 and the 111 forms of KCl and the most important forms of those compounds that could be adsorbed on them: PbCl2 (cotunnite), PbCl(OH) (laurionite–paralaurionite) and KCl·PbCl2 (challacolloite). Excellent lattice coincidences have been found, thus proving that the 111 KCl octahedron is largely privileged for adsorption/absorption to occur with respect to the 100 KCl cube. Based on this ground, simple kinetic considerations can be proposed to satisfactorily explain the observed morphology change.